HOUSEHOLD CHARACTERISTICS AND POTENTIAL INDOOR AIR POLLUTION ISSUES IN RURAL INDONESIAN COMMUNITIES USING FUELWOOD ENERGY - Haryono Setiyo Huboyo (Jurnal Ilmu Lingkungan, 2015)
Two rural communities using fuel wood energy in mountainous and coastal areas of Java island in Indonesia have been surveyed to know their household characteristics and the related potential indoor air pollution issues. By random sampling, we characterized fuel wood users only. The fuel wood use was mainly due to economic reason since some of the users were categorized as low-income families. Communities in the mountainous area were exposed to higher risk of indoor air pollution than those in coastal area due to their house characteristics and behavior during cooking. Both communities, however, were aware of indoor air pollution issues and indicated the sources. They also prioritized the factors to be controlled, which they perceived as the main cause of indoor air pollution problem.